PROBLEM BASED LEARNING MODELS ON STUDENTS' CRITICAL THINKING SKILLS ON RNA AND DNA STRUCTURE MATERIAL - Kesuma, Desvan Hardian; Haryati, Haryati; Syafitri, Anis (Universitas Negeri Medan, 2024)
This study aims to evaluate the effect of the Problem Based Learning (PBL) model on students' critical thinking skills in understanding the material of RNA and DNA structures. The PBL model is applied as an active learning approach that involves students in solving real problems and is relevant to the biology material being studied. This study used an experimental design with a control group and an experimental group where the experimental group was taught using the PBL model, while the control group used conventional learning methods. Data collection was carried out through critical thinking skills tests before and after the intervention, as well as observations during the learning process. The results of the analysis showed that students who were taught using the PBL model experienced a significant increase in critical thinking skills compared to the control group. These findings indicate that the application of the PBL model can improve students' understanding and analytical skills of the structure of RNA and DNA, and can be an effective alternative in the biology learning process in schools. This study provides recommendations for the wider application of the PBL method in the context of science education to improve students' critical thinking skills.